Business splitting: compliance with the principle of tax certainty in law enforcement practice - Karina A. Ponomareva (Правоприменение, 2020)
The subject. The problems of business splitting, when several new business entities are created on the basis of an existing organization in order to maintain a preferential special tax regime, are considered in the article.The aim of this paper is to find out criteria of unjustified tax benefit in the cases concerning business splitting.The methodology. The author uses methods of theoretical analysis, particularly the theory of integrative legal consciousness, as well as legal methods, including formal legal method and analysis of recent judicial practice.The main results, scope of application. The problems of assessing the circumstances of cases involving the application of a business splitting scheme by the taxpayer are inextricably linked to the assessment of the validity of the tax benefit. According to the author, splitting schemes should not be considered as tax evasion, but as an abuse of law. In addition, in order to substantiate the conclusion that a taxpayer has applied a business splitting scheme, the tax authority must have evidence that will indicate that the taxpayer has committed deliberate concerted actions together with persons under its control, aimed not so much at dividing the business as at obtaining an unjustified tax benefit as a result of using such a scheme. Judicial practice is quite ambiguous.Conclusions. The author comes to the conclusion that еhe key concept subject to criticism is the blurred criteria for obtaining tax benefits for taxpayers and the definition of the edge when it passes into the category of unjustified tax benefit.